Digital Token Valuation Cryptocurrencies, NFTs, Decentralized Finance, and Blockchains - Moro-Visconti, Roberto; Cesaretti, Andrea (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book looks at the analogic application of standard corporate valuation approaches to trendy digital tokens, expressed by cryptocurrencies, and validated through blockchain systems. Whereas traditional firm appraisal follows institutional guidelines and best practices, frontier research still must define the boundaries of these issues, linking a strong theoretical background to practical advances that still need finetuning. This book, written by an academic and a senior consultant, combines theoretical rigor with practical insights, providing an innovative framework for evaluators, managers, practitioners and academics of corporate valuation and financial technology. Roberto Moro-Visconti, MA and PhD, is professor of Corporate Finance at the Catholic University of the Sacred Heart, Milan, Italy, and is the director of studio Moro Visconti - chartered accountants and financial consultants. Dr. Moro-Visconti manages a consolidated financial boutique (www.morovisconti.com/en) that derives from a deep-rooted tradition of professional consultants in Milan and is specialized in the appraisal of digital intangibles and other assets. Andrea Cesaretti has worked for over thirty years in the field of administration and finance, collaborating with consulting firms, financial intermediaries, universities and training schools in Italy, the United States and Switzerland. He has held positions in Albertini Syz SGR, Alviero Martini, Anie, Anima SGR, Antonello Manuli Properties, the Italian Association of Precious and Related Stones Companies, Bugnion, Cacharel, Carnegie Italia, Kairos SGR, Ilva, IMQ, Pierrel, 3C Communications and Catholic University of the Sacred Heart of Milan, Italy.
1. Introduction -- 2. Asset Class Taxonomy and General Valuation Approaches -- 3. The Scalable Valuation of digital intangibles -- 4. Cryptocurrencies and Non-Fungible Tokens -- 5. Digital Art and Non-FungibleTokens -- 6. Blockchains, Internet of Value, and Smart Transactions -- 7. The Metaverse -- 8. Networking digital platforms and Virtual Marketplaces -- 9. Decentralized Finance (De.Fi.) -- 10. Cybersecurity -- 11. Digital Token Valuation: looking for a new Gold Standard? -- 12. The Cryptocurrency Crash of 2022: which lessons for the Future? -- 13. FinTech and Digital Payment Systems Valuation -- 14. Digitalization and ESG-driven Valuations.
Keywords: Financial engineering; Valuation; Business enterprises -- Finance; Financial Technology and Innovation; Investment Appraisal; Corporate Finance